A Review on Model and Control of Electromagnetic Active Engine Mounts - Henghai Zhang; Wenku Shi; Jun Ke; Guoyu Feng; Junlong Qu; Zhiyong Chen (Shock and Vibration)
The isolation of the body from engine vibration is the most challenging and disruptive vibrational problem. Active engine mounts (AEMs), especially electromagnetic AEMs, achieve a significant performance improvement in decreasing the wide frequency band vibration. Increasing research interest is necessary to provide the academic community with a guideline for electromagnetic AEMs. Therefore, the current review aims to comprehensively supplement the review of AEMs. The key reviews of electromagnetic AEMs focus on (1) general considerations of electromagnetic AEMs, (2) models, and (3) control strategies. This paper presents a review of the current status and developmental progress of AEMs. A theoretical model, a finite-element model, and the identification (or experimental modelling) of electromagnetic AEMs during the last 2 decades are then studied. Finally, control strategies, such as classical control, adaptive control, and two degree of freedom (2DOF) control, are discussed and compared. The main purpose of this paper is to meet the needs of researchers and engineers engaged in electromagnetic AEM analysis and control.